Exploring the Role of Environmental Impact in Maximizing the Effect of CSR on Profitability - Saeguso, Ellyzabeth Sonia; Santoso, Eko Budi (E-Jurnal Akuntansi; Vol 34 No 11 (2024), 2024)
This study aims to look at the effect of CSR on profitability and environmental impact as a moderating variable in the relationship between CSR and profitability. The method used in this study is a quantitative method with secondary data derived from sustainability reports of wholesale, retail, telecommunications, mining, transportation and public utility sector companies in 2022. Sample selection using purposive sampling method with a population of 148 companies listed on Osiris. The sample used was 124. This data is processed using multiple linear regression tests. The results showed that CSR has no significant effect on profitability proxied by NPM. Environmental impact does not moderate the relationship between CSR and profitability. Environmental impact has a positive effect on profitability which is a new discovery in the study. The results of this study can contribute to companies and investors in decision making.